Increased expression of inhibitor of apoptosis proteins, survivin and XIAP, in non-small cell lung carcinoma - Krepela, Evzen; Dankova, Petra; Moravcikova, Erika; Krepelova, Anna; Prochazka, Jan; Cermak, Jan; Schützner, Jan; Zatloukal, Petr; Benkova, Kamila (International journal of oncology, 2009)
Members of the inhibitor of apoptosis protein (IAP) family, survivin and X-chromosome-linked IAP (XIAP), contribute to apoptosis resistance of cancer cells, and an increase in their expression may elevate the apoptotic threshold of malignant tumours during their growth and progression. In the present study, we investigated the expression status of survivin and its interactants hepatitis B X-interacting protein (HBXIP) and XIAP in non-small cell lung carcinoma (NSCLC) cell lines and NSCLC tumours and matched lungs from surgically treated patients in relation to their clinicopathological data. The expression of survivin, HBXIP and XIAP mRNAs was quantitated by real-time RT-PCR. The expression of survivin and XIAP proteins was analysed by Western blotting and ELISA. Survivin mRNA and protein levels were highly upregulated in NSCLC cells and tissues as compared to the lungs. In fact, the levels of survivin mRNA and protein in the tumours were more than 10-fold higher in 96 (64%) and 72 (82%) of the 150 and 88 examined NSCLC patients, respectively. The expression of survivin mRNA was higher in squamous cell lung carcinomas than in lung adenocarcinomas (LACs; P=0.003) and in less-differentiated tumours than in well-differentiated ones (P=0.007). The level of survivin protein was higher in stage IB and stage II+III tumours (P=0.049 and P=0.044), than in stage IA tumours. The BIRC5 promoter polymorphism at nucleotide -31 did not influence the expression of survivin mRNA and protein in NSCLC cells and tumours. HBXIP mRNA was abundantly expressed in NSCLC cell lines and NSCLC tumours and lungs, while its level was comparable in the tumours and lungs. The expression of XIAP mRNA in NSCLC cell lines and NSCLC tumours and lungs was not significantly different. However, the expression of XIAP protein was higher in NSCLC tumours, particularly in LACs, as compared to the lungs (P=0.017 and P=0.004). In conclusion, the overexpression of survivin in the majority of NSCLCs together with the abundant or upregulated expression of HBXIP and XIAP suggest that tumours are endowed with resistance against a variety of apoptosis-inducing conditions.
Keywords: nádory plic; nemalobuněčný karcinom plic; exprese genu; Lung Neoplasms; Humans; survivin; messenger RNA; inhibitory apoptózy; Gene Expression; lidé středního věku; Carcinoma, Non-Small-Cell Lung; Female; Aged; adaptorové proteiny signální transdukční; dospělí; polymerázová řetězová reakce s reverzní transkripcí; ELISA; Blotting, Western; Inhibitor of Apoptosis Proteins; senioři; lidé; Adaptor Proteins, Signal Transducing; Reverse Transcriptase Polymerase Chain Reaction; X-Linked Inhibitor of Apoptosis Protein; Enzyme-Linked Immunosorbent Assay; Adult; RNA, Messenger; ženské pohlaví; Male; Middle Aged; proteiny asociované s mikrotubuly; stanovení celkové genové exprese; Survivin; X-vázaný inhibitor apoptózy; Gene Expression Profiling; western blotting; mužské pohlaví; Microtubule-Associated Proteins